Government Size, Supply Chain fiscal Decentralization Management, and Society Prosperity: A Data Panel Proof from Provinces in Indonesia - Khairudin Khairudin; Aminah Aminah; Sri Risma Yenny; Rahmawati Rahmawati; Dodi Setiawan (International Journal of Supply Chain Management, 2020)
The improvement of society prosperity can only be achieved if the regional government has sufficient resources, both in the form of financial and non-financial resources. This study aims to examine the effect of government size and supply chain fiscal decentralization on prosperity. This research was conducted in all provinces in Indonesia in the 2014-2018 period. Prosperityis measured by the human development index, which the source is from BPS-RI, the size of the regional government is measured by the total income earned in a year, and supply chain fiscal decentralization is measured through revenue sharing funds, general allocation funds, and special allocation funds sourced from BPK-RI. Testing was done with multiple linear regression and the results of the study showed that government size and supply chain fiscal decentralization have a positive and significant effect on prosperity. This finding is empirical evidence of the importance of government size as measured by regional income and supply chain fiscal decentralization for regional governments in order to accelerate the improvement of prosperity for prosperity.